PENGARUH KEBIJAKAN TRANSFORMASI DIGITAL TERHADAP PEMBANGUNAN DESA DI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Ash Shiddiq, M.Hasbi; ', Adianto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to determine the effect of village fund distribution on village infrastructure development. The research method used is a quantitative approach with a simple regression analysis technique. Primary data were obtained through documentation of village fund realization and infrastructure development, while secondary data were sourced from village reports. The results of the study show that the distribution of village funds has a significant effect on infrastructure development. This is evidenced by a positive regression coefficient and a significant t-test result. Thus, the greater the amount of village funds distributed, the higher the level of infrastructure development. Keywords: Village funds, infrastructure development, regression